Trends in autologous stem cell transplantation for newly diagnosed multiple myeloma: Changing demographics and outcomes in European Society for Blood and Marrow Transplantation centres from 1995 to 2019. (15th February 2022) - Swan, Dawn; Hayden, Patrick J.; Eikema, Dirk‐Jan; Koster, Linda; Sauer, Sandra; Blaise, Didier; Nicholson, Emma; Rabin, Neil; Touzeau, Cyrille; Byrne, Jennifer; Huynh, Anne; Cornelissen, Jan J.; et al.
Summary: Multiple myeloma (MM) accounts for 10% of haematological malignancies. Overall survival (OS) has improved in recent years due to increased use of autologous stem cell transplantation (ASCT) in the treatment of newly diagnosed MM and the advent of novel agents, including proteasome inhibitors, immunomodulatory drugs and monoclonal antibodies. To assess trends in ASCT including patient selection, choice of induction regimen, depth of response and survival, we performed a retrospective analysis of all patients undergoing first ASCT for MM in European Society for Blood and Marrow Transplantation centres between 1995 and 2019. A total of 117 711 patients across 575 centres were included. The number of transplants performed increased sevenfold across the study period. The median age increased from 55 to 61 years, and the percentage of patients aged >65 years rose from 7% to 30%. Use of chemotherapy‐based induction fell significantly, being largely replaced by bortezomib‐based regimens. The two‐year complete response rate increased from 22% to 42%. The five‐year progression‐free survival and OS rates increased from 28% to 31% and from 52% to 69%, respectively. Transplant mortality fell from 5.9% to 1.5%. Ongoing advances in MM treatment may challenge the future role of ASCT. However, at the current time, ASCT remains central to the MM treatment paradigm.